(untitled) (Jurnal Manajemen Bisnis, 2020)
The influence of the image on the existence of nation branding is very important to the decision of ASEAN tourists who want to visit Indonesia, especially at Lake Toba in Samosir. This study aims to determine the effect of nation branding strategy on tourists who want to visit Lake Toba, especially seen from the Occupancy hotel that has been visited. The method of this research uses descriptive qualitative. From the research results obtained by using an independent variable, namely nation branding consisting of people, torurism, cuture, heritage and for the dependent variable, the decision of tourists visiting. From the results obtained through the validity test for people the value of r is 0.444, for r tourism is 0.444, for culture r is 0.474 and for culture r is 0.568. From the results above it can be interpreted that it is valid, where if the value of validates r each question is greater than 0.361 so it can be concluded the results of the variables obtained are valid.